Integration and Identities: The Effects of Time, Migrant Networks, and Political Crises on Germans in the United States. (1st October 2018) - Krawatzek, Félix; Sasse, Gwendolyn
Abstract: This article offers the first large-scale analysis of the interlinked dynamics of integration and belonging based on perceptions of "ordinary" German-speaking migrants in the United States in the nineteenth and twentieth centuries. Our analysis draws on a corpus of over a thousand letters from the North American Letter Collection held at the Forschungsbibliothek Gotha in Germany. Through computer-assisted text analysis, framed by research on transnationalism and immigrant integration, we explore patterns in integration and identities over time. We show how the migrants continuously redefine their identities vis-à-vis their homeland and the host society, and their letters thereby shape the image of the United States and the homeland for their recipients. Our analysis establishes more comprehensively than have previous historical and social science studies that integration into a host society is a non-linear process. Immigrant identities are influenced less by the time they have spent in the receiving country than by critical political events that affect both the country of origin and that of destination. Such events can reactivate migrant's identifications with their homeland. Immigrant networks filter this dual process in that they can facilitate migrants' integration while also reminding them of people and places left behind.